Technology-Supported Teaching Interventions and Student Computational Thinking: A Meta-Analysis Based on 37 Empirical Studies - Zhou, Qin (Best Evidence in Chinese Education, 2023)
Computation thinking, which integrates a wide variety of thinking activities such as problem-solving, system design, and comprehending human behavior, has become a critical thinking ability in the context of accelerated digital transformation. Numerous studies from various counties posited that technology-supported teaching interventions (TSTI) had the potential to foster the development of computational thinking skills in students, whereas some suggested that the potential was insignificant. This article employed the meta-analytical technique to research into 37 domestic and foreign empirical studies published between January 2006 and October 2022, with a focus on examining the impact of TSTIs on student computational thinking.